1968
DOI: 10.1084/jem.127.2.307
|View full text |Cite
|
Sign up to set email alerts
|

The X-Y-Z Scheme of Immunocyte Maturation

Abstract: The response of an animal to antigen is altered after its first exposure. The intensified secondary response has been attributed by some to the presence of qualitatively different "memory" cells. The concept of two types of antigen-sensitive ceils, occurring as successive stages in immunoeyte maturation, was elaborated by Burner (i) and Leduc et al. (2), and later into an X-Y-Z scheme by Sercarz and Coons (3). In the X-Y-Z formulation, the X ceil is the first antigen-sensitive ceil in the lymphocytic series… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
11
0

Year Published

1970
1970
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(15 citation statements)
references
References 24 publications
4
11
0
Order By: Relevance
“…This demonstration that antigenic interactions of primary and secondary precursor cells differ qualitatively extends the implications of several other investigators who found evidence for such a difference in the relative ease of stimulation, particularly in vitro, of secondary cells (16,19,40). Since most natural antigens present repeating determinants, the fact that secondary cells probably possess multivalent receptors may have considerable biological significance since the avidity of such cells for these antigens would be markedly ncreased over that of primary cells (41).…”
Section: Comparative Properties Of Precursor Cells From Immune and Nosupporting
confidence: 64%
“…This demonstration that antigenic interactions of primary and secondary precursor cells differ qualitatively extends the implications of several other investigators who found evidence for such a difference in the relative ease of stimulation, particularly in vitro, of secondary cells (16,19,40). Since most natural antigens present repeating determinants, the fact that secondary cells probably possess multivalent receptors may have considerable biological significance since the avidity of such cells for these antigens would be markedly ncreased over that of primary cells (41).…”
Section: Comparative Properties Of Precursor Cells From Immune and Nosupporting
confidence: 64%
“…Our results further support the concept that there are definite functional differences between these two types of B cells. It is still controversial whether AFC and memory cells are generated from the same precursor cells through asymmetric cell divisions or from different precursor cells (B cells at different maturation stages) through symmetric cell divisions (2). Our present finding that CPS-K acts to inhibit almost selectively the generation of RFC response but not PFC responses to antigen when CPS-K and SRBC were administered simultaneously to SRBCprimed mice strongly supports the latter concept.…”
Section: Discussionsupporting
confidence: 79%
“…32 and 56). Immunological history shapes the T cell repertoire that will be involved in the response to a new pathogen through heterologous priming of T cells by cross-reactive pathogen(s) (57) or by exhaustion of immune repertoires (6,(58)(59)(60). We show in this study that differences in the molecular environment in which an epitope is contained resulted in a small variation of the determinants effectively presented.…”
Section: Discussionmentioning
confidence: 84%